Electroacupuncture Potentiates Cannabinoid Receptor-Mediated Descending Inhibitory Control in a Mouse Model of Knee Osteoarthritis - Yuan, Xiao-Cui; Zhu, Bing; Jing, Xiang-Hong; Xiong, Li-Ze; Wu, Cai-Hua; Gao, Fang; Li, Hong-Ping; Xiang, Hong-Chun; Zhu, He; Zhou, Bin; He, Wei; Lin, Chuan-You; et al. (Frontiers in Molecular Neuroscience, 2018)
Knee osteoarthritis (KOA) is a highly prevalent, chronic joint disorder, and it is a typical disease which can develop chronic pain. Although electroacupuncture (EA) is effective in relieving chronic pain in clinic, the involved mechanisms remain unclear. Reduced diffuse noxius inhibitory controls (DNIC) function is associated with chronic pain, and which may be related to the deficit of endocannabinoids. In the present study, we determine whether EA may potentiate cannabinoid receptor mediated descending inhibitory control and inhibit chronic pain in a mouse model of KOA. We found that the optimized parameters of EA inhibiting chronic pain was low frequency and high intensity (2 Hz+1 mA). EA reversed the reduced expression of CB1 receptors and the 2-AG level in the midbrain in chronic pain. Microinjection of the CB1 receptor antagonist AM251 into the ventrolateral periaqueductal gray (vlPAG) can reversed the EA effect on pain hypersensitivity and DNIC function. In addition, CB1 receptors on GABAergic but not glutamatergic neurons are involved in the EA effect on DNIC function and descending inhibitory control of 5-HT in medulla, thus inhibiting chronic pain. Our data suggest that endocannbinoid (2-AG)-CB1R-GABA-5-HT may be a novel signaling pathway involved in the effect of EA improving DNIC function and inhibiting chronic pain.